Re-evaluating Immediate, Adjuvant, and Salvage Intravesical Chemotherapy in Non-Muscle-Invasive Bladder Cancer: A Systematic Review and Meta-Analysis of Gemcitabine Non-Inferiority to Mitomycin C - Reza Abdia Jauhari (Archives of The Medicine and Case Reports, 2026)
Non-muscle-invasive bladder cancer demonstrates a uniquely high propensity for recurrence following initial transurethral resection of bladder tumor. A single, immediate post-operative instillation of chemotherapy became the established standard to mitigate this risk. Mitomycin C historically functioned as the agent of choice; however, frequent drug shortages and significant local toxicity profiles necessitated the rigorous evaluation of viable alternatives. Gemcitabine, a pyrimidine nucleoside analogue, emerged as a promising candidate. This study aimed to evaluate the comparative efficacy and safety of gemcitabine versus mitomycin C across immediate post-operative, adjuvant, and salvage clinical settings. A systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. The analysis utilized data from seven key comparative trials evaluating gemcitabine versus mitomycin C. A highly specific search strategy isolated direct head-to-head comparative studies. Data extraction focused exclusively on recurrence rates, time to recurrence, and adverse events. Pooled Odds Ratios and Standardized Mean Differences were calculated using a DerSimonian-Laird random-effects model. Sensitivity analyses isolating randomized controlled trials and excluding upper tract urothelial carcinoma data were explicitly performed. Five primary studies provided head-to-head comparative data for recurrence, comprising 405 patients. Two additional studies evaluated sequential salvage therapy. Adjuvant gemcitabine regimens demonstrated a significant reduction in recurrence compared to mitomycin C (Odds Ratio 0.38, 95 percent Confidence Interval 0.19 to 0.75). In strictly immediate single-dose settings, mitomycin C demonstrated a trend toward superior recurrence prevention over gemcitabine (Odds Ratio 1.65). Toxicity analysis heavily favored gemcitabine, showing a significantly lower incidence of chemical cystitis (Odds Ratio 0.22). Sequential salvage therapy yielded a 30 percent to 37 percent long-term recurrence-free survival. In conclusion, gemcitabine demonstrated non-inferiority to Mitomycin C regarding overall oncological safety and exhibited a markedly superior tolerability profile. Mitomycin C retained a marginal advantage in the strict immediate post-operative window due to its potent cell-cycle-independent action. However, Gemcitabine's efficacy in adjuvant settings and favorable side-effect profile established it as a highly rational alternative.